Digitalizing Construction Monitoring (DCM): an overview of Malaysian construction industry and proposing prototype software - Ahmed Memon, Zubair; Abd. Majid, Muhd. Zaimi; Mustaffar, Mushairry (2006)
Real-time monitoring and control on construction site is a growing field and still in its infancy. Managing project information during the construction phase is an important task yet difficult task, currently; however, the construction industry relies heavily on written reports to document site conditions, which requires good writing skills and unbiased judgments. Manual monitoring of construction sites is costly and error prone. A persistent problem in construction is to develop the as-built actual physical progress schedule of construction scene. Consequently, this study addresses Digitalizing Construction Monitoring (DCM) model for monitoring and evaluating the physical progress of the project. A pilot survey was carried within Malaysian Construction Industry to investigate the common methods and processes of project progress evaluating and monitoring and utilization of existing computer based application system for monitoring project progress performances. The research reported in this paper focuses on the issue related to digitalizing the project progress monitoring and proposing prototype software, which integrate the AutoCAD drawings and digital images. User can retrieves the project information in form of images and by using photogrammetry techniques every detail of building should be precisely documented to obtain reliable measurement from photographs and simulated with CAD drawings to develop the physical progress report. By introducing the DCM at the construction phase it allows the resident engineer, project manager, construction manager, and site manager to develop the physical progress report of construction and helps in decision making. This system bridge the gap for monitoring and controlling the construction work by implementing the information technology techniques.